Discourage the grade retention. Advice from the Educational Inspection on students’s promotion decision - Luna Ariza, Pedro Ángel (Avances en Supervisión Educativa, 2018)
The grade retention is a teacher´s standard decision that intends to level the students´s school performance by staying one more year in same educational grade/year. The recurrent use of this measure is part of the educational culture in Spain which causes an important differential in compare with the rates of others countries. Recently research questions the effectiveness of the grade retention coming to consider it worsens student performance. This article aims to synthesize the main evidence on the subject and provide alternative measures for education inspectors to advise in school´s improvement.
Keywords: grade retention; advice; educational inspection; school performance